ADMINISTRATIVE CONTRACT IN THE LEGAL SYSTEM OF UKRAINE: ISSUES, WAYS OF IMPROVEMENT, AND INTERNATIONAL EXPERIENCE - Bezzubov, Dmytro; Andriiash, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article: Improving the institution of an administrative agreement based on identifying problems of conclusion, implementation, scope, features of the legal nature of this agreement, as well as borrowing positive international experience in its application. Research methods: comparative legal method, analysis and synthesis, formal legal method were used. Results: it was found that an administrative agreement is an effective tool for regulating administrative and legal relations, which helps to implement the performance of certain functions by subjects of authority. It was found that the legislation of Ukraine does not sufficiently regulate the contract under study, which causes discussions in the scientific community and generates different approaches in legal and, in particular, judicial practice in resolving disputes arising from administrative contracts. It is proposed to borrow Germany’s experience regarding the implementation of an administrative agreement and to amend the Law of Ukraine "On Administrative Procedure", where it is necessary to clearly define the grounds for concluding an administrative agreement, its amendments, termination, requirements for form, and other important criteria. Discussion: scope of application of an administrative agreement; control over the implementation of an administrative agreement; subordination relations in an administrative agreement. An administrative agreement in the system of public-legal relations is of great importance, since with the help of such an agreement certain functions of executive bodies can be implemented. Today, the issue of an administrative agreement arises in connection with Ukraine’s European integration and relevant reforms in the field of public law, because the practice of administrative agreements is widespread in EU countries, and there is a corresponding clear legal regulation for their application. In Ukraine, there are a number of problems related to the application of an administrative contract that require study and resolution. One of them is the problem of imperfect and contradictory special legislation, and therefore, subjects who have expressed a desire to conclude an administrative contract must be guided by the general provisions on the conclusion of contracts, in particular, Book Five of the Civil Code of Ukraine (hereinafter referred to as the Civil Code of Ukraine). However, the Civil Code of Ukraine does not take into account the specifics of the parties to the contract under study and its content. In judicial practice, courts are guided by the concept defined in the Code of Administrative Procedure of Ukraine (hereinafter referred to as the Code of Administrative Procedure of Ukraine) and the same provisions (general) that are specified in the Civil Code of Ukraine, which significantly complicates the resolution of disputes arising from administrative contracts.